Effects of simulated weightlessness on thermal sweating of human body: An experimental study. Issue 1 (January 2019) - Zhu, Hui; Wang, Hanqing; Yu, Chuck; Liu, Zhiqiang
Thermal sweating is the thermoregulatory activity of the human body in hot and warm environments, which is critical to the human thermal comfort and health. The sweating of a human body in a real weightlessness environment has seldom been researched, and simulated weightlessness has usually been conducted under comfortable environments. In order to study the sweating of the human body under weightlessness, a 7-day −6° head down bed rest experiment was carried out on six male subjects lying on their backs to simulate the physiological changes that occur under a weightless environment. The skin microcurrents of the subjects were recorded to evaluate sweating under a range of environments. The results showed that sweating was more significant in the torso and head areas than on the arms and lower body. The whole body sweat rates of subjects were lower than those before the simulated weightlessness experiment. However, the threshold air temperature for the onset of sweating under simulated weightlessness was higher than that before the simulation. This was possibly due to the raising of thermoregulatory set-point temperature of the body. Findings have shown that the sweating behaviour and thermal response of a male human body in a weightless environment could be different to those in the terrestrial condition.